A PELATIHAN DASAR PENGGUNAAN AI GENERATIF UNTUK MEMBANTU PRODUKSI KONTEN UMKM - Widyastuti Andriyani; Prisilia Talakua; Lisa Astria Milasari; Firman Noor Hasan (Forum Komunikasi Dosen, 2025)
The purpose of this community service research is to measure the effectiveness of basic training on the use of generative AI in assisting content production for MSMEs in Yogyakarta. This training was designed to address the main challenges faced by MSMEs, namely limited resources and expertise in creating consistent and high-quality digital marketing content. Through an interactive workshop method focused on hands-on practice, 25 MSME actors were educated on the concept of generative AI, prompt engineering techniques, and the utilization of AI tools. The evaluation results showed a significant increase in participant understanding, content quality, and time efficiency, where participant understanding jumped from 15% to 95%, content quality increased by 60%, and time efficiency improved by 40%. In conclusion, this training proves that the integration of generative AI is an effective strategic solution for empowering MSMEs, enhancing their competitiveness, and fostering sustainable business growth in the digital era.